Prince, People, and Confession : the Second Reformation in Brandenburg - Nischan, Bodo (University of Pennsylvania Press, 2016)
A religious study of the attempts made by the rulers of the territories of Brandenburg, Germany, to move from Lutheranism to Reformed theology and practice, and the resistance with which these efforts were met by the clergy, lay leaders, and citizens.